Cancer epitranscriptomics in a nutshell. (August 2022) - Primac, Irina; Penning, Audrey; Fuks, François
Abstract : Remarkable technological progress has led to breakthrough discoveries in epitranscriptomics, reshaping our understanding of modifications decorating RNA. The past decade has seen a tremendous endeavor to describe the nature, functions, and biological roles of messenger RNA (mRNA) modifications, positioning epitranscriptomics as a crucial pillar in tumor biology. Like DNA and histone modifications, mRNA marks have been increasingly linked to cancer pathogenesis. Here, we summarize the latest research in cancer epitranscriptomics with emphasis on N6-methyladenosine, untangling its contribution to five prime oncogenic features: tumor growth, activating invasion and metastasis, stemness, metabolic reprogramming, and tumor microenvironment. We discuss mRNA-modifying enzymes, their impact on biological processes, and contribution to cancer hallmarks. We spotlight epitranscriptomics as a promising bonanza for forthcoming targeting approaches in cancer therapy.